A Jónás-komplexus elmélet: avagy a bibliai Jónás könyve elemzése pszichológiai szempontok alapján - Vanderstein, Noémi (Jelenkori Társadalmi és Gazdasági Folyamatok, 2012)
This paper introduces one of the aspects concerning the Book of Jonah in the Bible. The book can be interpreted in a number of ways. My aim is to show how Dr. Abraham Maslow makes an analysis on the main character of the story. Jonah’s personality changes in the story. He faces some adventures which result in losses and profits at the same time. My aim is to present a new wave in the field of psychology. It is called the Jonah Complex. This trend originates from the 1960s, and the basis of the theory is the subject of Jonah. Everybody in the world has a part of Jonah in himself or herself but probably we do not recognize the symptoms in ourselves.